Desenvolvimento de micropartículas poliméricas inteligentes para liberação modi cada do praziquantel para o tratamento da esquistossomose - Paiva, Thamiris Franckini (2019)
Schistosomiasis is one of the major public health problems worldwide. Although this is a common illness in preschool children, the treatment is carried out through the administration of praziquantel (PZQ) tablets, which are characterized by a strong bitter taste. The main objective of the present work is the development of a new PZQ oral formulation, with the use of smart microparticles for the encapsulation and subsequent release of the drug in the body. The suspension polymerization technique was used for the synthesis of the polymer microparticles of PMMA and copolymers P(MMA-co-DEAEMA) and P(MMA-co-DMAEMA), in the presence of PZQ, having mean diameter between 80 and 400 µm with high encapsulation e ciencies (> 90 %) and release rates close to 100 % after 1 hour of assay, with signi cant in uence of the comonomer content and particle diameter on the drug release rate. In addition, the in vivo tests showed that the smart microparticles reached plasma concentrations higher than the pure PZQ, indicating the increased bioavailability of PZQ.